Development of information support for simulation of the process of deformation of root polymer plate in book blocks sewed with threads - Paliukh, Oleksandr; Kyrychok, Petro; Shtefan, Yevheniy; Titov, Andrii (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this study is the processes of deformation of the root polymer plate reinforced with stitches of threads with preliminary tension in book blocks sewn with threads. The analytical and experimental studies reported here are based on the application of the methodology for developing a simulation model of the process of deforming the adhesive polymer plate. The basic assumption of the study is that the use of information support for simulation modeling will contribute to the improvement of the structural and technological parameters of the root part of the book blocks sewn with threads. This cannot be achieved without analyzing and decomposition of the technical system of the book block, classifying subsystems and describing them in the form of a finite set of classes and the connections between them. A procedure for determining the mechanism of interaction of elements of the root part of book blocks sewn with threads is proposed. It is shown that the residual cyclic deformation of the adhesive plate and the stitches of the implanted threads depends on the strength of the bonds between the elements of the joined structure of the materials. It also depends on the number of cycles of discrete loads heterogeneous in terms of dimensional indicators and the place of their application. This is due to the fact that stitches of threads are only partially implanted into the structure of the adhesive plate, the other part that fastens the folds of notebooks is outside the adhesive plate. The influence of cyclic loads applied at different angles relative to the stitches of the threads was revealed. The angular discrepancy fluctuates, in the case of using PVAD D51C glue, in the range of 0.735–0.907, and, for Technomelt GE3636 thermal glue, 0.913–0.940. The developed simulation model of the processes of deformation of the root polymer plate makes it possible to determine the mechanism of interaction of the elements of the root part of the book blocks and predict the durability of the product